The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1159/000096217
|View full text |Cite
|
Sign up to set email alerts
|

Two Genetic Rat Models of Arterial Hypertension Show Different Mechanisms by Which Adult Hippocampal Neurogenesis Is Increased

Abstract: To investigate strain differences and genetic effects on different aspects of neurogenesis, we compared young adult spontaneously hypertensive/hyperactive rats (SHR) and stroke-prone SHR (SHRSP) with the genetic control WKY strain. In both hypertensive/hyperactive strains, the number of newly generated neurons and the number of lineage-determined cells as detected by doublecortin (DCX) immunoreactivity were significantly increased. SHRSP had significantly more DCX-positive cells than the other groups. Whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 102 publications
1
19
1
Order By: Relevance
“…This result concurs with previous studies which found that neurogenesis dramatically declined in the dentate gyrus during aging [5,7,11,12,17,23,25,28]. In addition, Kronenberg et al [16] compared young adult SHR and stroke-prone SHR (SHRSP) with the genetic control WKY strain: in both SHR and SHRSP, newly generated DCX immunoreactive neurons were significantly high compared to WKY strain. However, in the present study, we found that the number of DCX immunoreactive cells, the intensity of DCX immunoreactivity and the expression level of DCX protein in the SHRs were higher than those in the SDRs at corresponding age stages.…”
Section: Discussionsupporting
confidence: 91%
“…This result concurs with previous studies which found that neurogenesis dramatically declined in the dentate gyrus during aging [5,7,11,12,17,23,25,28]. In addition, Kronenberg et al [16] compared young adult SHR and stroke-prone SHR (SHRSP) with the genetic control WKY strain: in both SHR and SHRSP, newly generated DCX immunoreactive neurons were significantly high compared to WKY strain. However, in the present study, we found that the number of DCX immunoreactive cells, the intensity of DCX immunoreactivity and the expression level of DCX protein in the SHRs were higher than those in the SDRs at corresponding age stages.…”
Section: Discussionsupporting
confidence: 91%
“…Higher glucocorticoid levels and reduced 5-HT signaling [Veenema et al, 2003[Veenema et al, , 2004Veenema and Neumann, 2007] in the LAL mice might be contributing to this difference. Genetic influence on hippocampal neurogenesis has also been shown in several other studies [Hayes and Nowakowski, 2002;Kempermann and Gage, 2002;Schauwecker, 2006;Kronenberg et al, 2007]. The observation that social stress affects neurogenesis [Gould et al, 1997] and structural plasticity in the brain [Magarinos et al, 1996;Fuchs and Flügge, 2003] has received wide attention, but the possible interaction between these effects and pre-existing differences in stress coping style is less studied.…”
Section: Linking Physiological Behavioral and Cognitive Traits -Possmentioning
confidence: 79%
“…Hippocampal cell counts were determined in one-in-six series of sections covering the entire hippocampus in its rostrocaudal extension as described previously (Kronenberg et al, , 2007. Briefly, cells located in the granule cell layer and adjacent subgranular zone, defined as a two-cell bodies-wide zone of the hilus along the base of the granule cell layer were counted (Brown et al, 2003 Synaptosomes were prepared as described previously (Fink et al, 2002a,b) from the neocortex or hippocampus of adult Gsn ϩ/ϩ or Gsn Ϫ/Ϫ mice.…”
Section: Quantification and Imagingmentioning
confidence: 99%
“…DCX-immunoreactive cells and the number of CR-immunoreactive cells were used as surrogate markers of neurogenesis (Fig. 2C,D) (Kempermann et al, 2004;Kronenberg et al, 2007Kronenberg et al, , 2008. Both the number of DCX ϩ cells and the number of CR ϩ cells were robustly increased in gelsolin-deficient animals compared with wild-type controls (Fig.…”
Section: The Increase In Hippocampal Neurogenesis Is Preserved In Agementioning
confidence: 99%